Avifauna de los bosques de cactáceas columnares del Valle de Tehuacan, Puebla - Del Coro Arizmendi, María; Espinosa De Los Monteros, Alejandro (Instituto de Ecología, A.C., 1996)
We present a list of the avifauna of the columnar cacti forests of central México in the Tehuacán Valley. We found 90 species grouped into 13 orders and 27 families. Residents (56 species) are mostiy species of insectivorous and frugivorous-granivorous birds. Migrant birds are aiso pnmarily insectivorous. Another group of species moves locally between habitats during time of resource abundance. These species are common to the surrounding tropical deciduous forests that move constantly between habitats. The avifauna of the Tehuacan Valley share about 30% of the species with North American deserts (Sonoran, Chihuahuan, Mohave and Great Basin) and 33% with tropical deciduous forests in México. This assemblage of species from different habitats is probably the cause of the high bird diversity found in the Valley.